Kynurenine is an endothelium-derived relaxing factor produced during inflammation - Wang, Yutang; Liu, Hanzhong; McKenzie, Gavin; Witting, Paul K; Stasch, Johannes-Peter; Hahn, Michael; Changsirivathanathamrong, Dechaboon; Wu, Ben J; Ball, Helen J; Thomas, Shane R; Kapoor, Vimal; Celermajer, David S; et al. (Nature medicine, 2010)
Kynurenine, a metabolite produced by the action of the enzyme indoleamine 2,3-dioxygenase on tryptophan, accumulates under inflammatory conditions and has immunomodulatory effects. This study by Yutang Wang et al . describes a new function for kynurenine as an endogenous vasodilator under conditions of systemic inflammation, such as malaria infection and endotoxemia in mice, and provides insight into the molecular mechanisms involved ( pages 265–267 ). Control of blood vessel tone is central to vascular homeostasis. Here we show that metabolism of tryptophan to kynurenine by indoleamine 2,3-dioxygenase (Ido) expressed in endothelial cells contributes to arterial vessel relaxation and the control of blood pressure. Infection of mice with malarial parasites ( Plasmodium berghei ) or induction of endotoxemia in mice led to endothelial expression of Ido, decreased plasma tryptophan concentration, increased kynurenine concentration and hypotension. Pharmacological inhibition of Ido increased blood pressure in systemically inflamed mice but not in mice deficient in Ido or interferon-γ, which is required for Ido induction. Both tryptophan and kynurenine dilated preconstricted porcine coronary arteries; the dilating effect of tryptophan required the presence of active Ido and an intact endothelium, whereas the effect of kynurenine was endothelium independent. The arterial relaxation induced by kynurenine was mediated by activation of the adenylate and soluble guanylate cyclase pathways. Kynurenine administration decreased blood pressure in a dose-dependent manner in spontaneously hypertensive rats. Our results identify tryptophan metabolism by Ido as a new pathway contributing to the regulation of vascular tone.